Unveiling and harnessing the human gut microbiome in the rising burden of non-communicable diseases during urbanization - Huang, Ziyu; Li, Yue; Park, Heekuk; Ho, Martin; Bhardwaj, Kanchan; Sugimura, Naoki; Lee, Hye Won; Meng, Huicui; Ebert, Matthias; Chao, Kang; Burgermeister, Elke; Bhatt, Aadra P.; et al. (Gut microbes, 2023)
The world is witnessing a global increase in the urban population, particularly in developing Asian and African countries. Concomitantly, the global burden of non-communicable diseases (NCDs) is rising, markedly associated with the changing landscape of lifestyle and environment during urbanization. Accumulating studies have revealed the role of the gut microbiome in regulating the immune and metabolic homeostasis of the host, which potentially bridges external factors to the host (patho-)physiology. In this review, we discuss the rising incidences of NCDs during urbanization and their links to the compositional and functional dysbiosis of the gut microbiome. In particular, we elucidate the effects of urbanization-associated factors (hygiene/pollution, urbanized diet, lifestyles, the use of antibiotics, and early life exposure) on the gut microbiome underlying the pathogenesis of NCDs. We also discuss the potential and feasibility of microbiome-inspired and microbiome-targeted approaches as novel avenues to counteract NCDs, including fecal microbiota transplantation, diet modulation, probiotics, postbiotics, synbiotics, celobiotics, and precision antibiotics.
Gesehen am 15.04.2024